Direct numerical simulation of a turbulent boundary layer over an oscillating wall - Govindaraju, Vitul Raj. (2013)
This study aims to decipher if the current rise of China and tensions in the South China Sea mark the beginning of an increasingly assertive claim of “indisputable sovereignty” on the part of China, and its implications to the other stakeholders. Focusing on China’s behavior within the South China Sea disputes, this thesis investigates the dominance of power calculations and interest considerations, interacting within a Power and Interest Nexus, when seeking to understand China’s behavior in dealing with the disputes in the South China Sea. By revisiting past incidents and essentializing the conditions of the disputes in the South China Sea, the thesis argues that China’s interests, ofboth pragmatic and identity origins, need to coincide with distinct power conditions, before assertive and decisive actions are taken. In order to understand China’s behavior, the study provides a comprehensive investigation into the dynamic nature of China’s national interest considerations - on sovereignty, national security, economy and regime legitimacy - and interacts them with comparative power calculations vis-a-vis direct and indirect opponents. Overlaying the analysis through the power-interest nexus framework on present day situations, the thesis finally explores the prospects of China’s rising assertiveness and conditions for stability in the South China Sea disputes.